Exchange coupling in a thiocyanato-bridged copper(II) chain: Computational approach to magnetostructural correlations. (1st November 2021) - Martínez, Lorena; Veiga, Nicolás; Bazzicalupi, Carla; Bianchi, Antonio; Lloret, Francesc; Kremer, Carlos; Chiozzone, Raúl
Graphical abstract: Abstract: In this article we report the synthesis and magneto-structural characterization of two new copper(II) compounds with thiocyanato and methyl(2-pyridil) ketone oxime (mpkOH), namely [Cu(NCS)(mpkO)(mpkOH)] (1 ) and [Cu(µ-NCS)(NCS)(mpkOH)] n (2 ). Compound 1 is a mononuclear complex that crystallizes as discrete units. Conversely, compound 2 is a single equatorial-axial end-to-end thiocyanato bridged polymeric chain of Cu(II) with the oxime as a co-ligand. The coordination geometry around the Cu(II) centers is distorted square pyramidal for 1 and 2. The magnetic susceptibility data for 2 reveal weak intrachain antiferromagnetic coupling, with J value −0.74(3) cm −1 and g  = 2.10(1). The application of computational tools to a binuclear model of 2 allowed us to unveil the structural basis that modulates the magnetic behavior of this type of thiocyanato-bridged Cu(II) chains. The results suggest that although small values of J are expected, the strongest ferromagnetic interactions can be obtained by including co-ligands that trigger a squared-based pyramidal-to-trigonal bipyramidal distortion of the coordination polyhedra.